Hydrothermal carbonization for the preparation of hydrochars from glucose, cellulose, chitin, chitosan and wood chips via low-temperature and their characterization. (December 2017) - Simsir, Hamza; Eltugral, Nurettin; Karagoz, Selhan
Highlights: Hydrochar formation from different biomass was studied. Two different spherical hydrochar structures were formed: hard sphere and densely-aggregated form. Completed carbonization of glucose yielded uniform-sized particles. The average sizes of carbon spheres using glucose and chitosan were found as 560 and 42 nm, respectively. Abstract: In this work, the hydrothermal carbonization of glucose, cellulose, chitin, chitosan and wood chips at 200 °C at processing times between 6 and 48 h was studied. The carbonization degree of wood chips, cellulose and chitosan obviously increases as function of time. The heating value of glucose increases to 88% upon carbonization for 48 h, while it is only 5% for chitin. It is calculated to be between 44 and 73% for wood chips, chitosan and cellulose. Glucose yielded complete formation of spherical hydrochar structures at a shorter processing time, as low as 12 h. However, carbon spheres with narrow size (∼560 nm) distribution were obtained upon 48 h of residence time. Cellulose and wood chips yielded a similar morphology with an irregular size distribution. Chitin seemed not to undergo hydrothermal carbonization, whereas densely aggregated spheres of a uniform size around 42 nm were obtained from chitosan after 18 h.